(untitled) (Modern education and development, 2025)
This article explores the phenomenon of homonymic and synonymic affixes in the English language. Homonymic affixes are those that have the same form but different meanings or functions, while synonymic affixes differ in form yet convey similar meanings. The paper provides definitions, explanations, and illustrative examples to help readers understand how these affixes contribute to word formation and semantic diversity in English. This study is useful for linguists, language learners, and teachers interested in morphology and vocabulary development.